Indication Criteria for Total Knee Arthroplasty in Patients with Osteoarthritis – A Multi-perspective Consensus Study - Schmitt, Jochen; Lange, Toni; Günther, Klaus-Peter; Kopkow, Christian; Rataj, Elisabeth; Apfelbacher, Christian; Aringer, Martin; Böhle, Eckhardt; Bork, Hartmut; Dreinhöfer, Karsten; Friederich, Niklaus; Frosch, Karl-Heinz; Gravius, Sascha; Gromnica-Ihle, Erika; Heller, Karl-Dieter; Kirschner, Stephan; Kladny, Bernd; Kohlhof, Hendrik; Kremer, Michael; Leuchten, Nicolai; Lippmann, Maike; Malzahn, Jürgen; Meyer, Heiko; Sabatowski, Rainer; Scharf, Hanns-Peter; Stoeve, Johannes; Wagner, Richard; Lützner, Jörg (Zeitschrift für Orthopädie und Unfallchirurgie, 2017)
Background and Objectives Knee osteoarthritis (OA) is a significant public health burden. Rates of total knee arthroplasty (TKA) in OA vary substantially between geographical regions, most likely due to the lack of standardised indication criteria. We set out to define indication criteria for the German healthcare system for TKA in patients with knee OA, on the basis of best evidence and transparent multi-stakeholder consensus.Methods We undertook a complex mixed methods study, including an iterative process of systematic appraisal of existing evidence, Delphi consensus methods and stakeholder conferences. We established a consensus panel representing key German national societies of healthcare providers (orthopaedic surgeons, rheumatologists, pain physicians, psychologists, physiotherapists), payers, and patient representatives. A priori defined consensus criteria were at least 70% agreement and less than 20% disagreement among the consensus panel. Agreement was sought for (1) core indication criteria defined as criteria that must be met to consider TKA in a normal patient with knee OA, (2) additional (not obligatory) indication criteria, (3) absolute contraindication criteria that generally prohibit TKA, and (4) risk factors that do not prohibit TKA, but usually do not lead to a recommendation for TKA.Results The following 5 core indication criteria were agreed within the panel: 1. intermittent (several times per week) or constant knee pain for at least 3 – 6 months; 2. radiological confirmation of structural knee damage (osteoarthritis, osteonecrosis); 3. inadequate response to conservative treatment, including pharmacological and non-pharmacological treatment for at least 3 – 6 months; 4. adverse impact of knee disease on patientʼs quality of life for at least 3 – 6 months; 5. patient-reported suffering/impairment due to knee disease. Additional indication criteria, contraindication criteria, and risk factors for adverse outcome were also agreed by a large majority within the multi-perspective stakeholder panel.Conclusion The defined indication criteria constitute a prerequisite for appropriate provision of TKA in patients with knee OA in Germany. In eligible patients, shared-decision making should eventually determine if TKA is performed or not. The next important steps are the implementation of the defined indication criteria, and the prospective investigation of predictors of success or failure of TKA in the context of routine care provision in Germany.Hintergrund und Zielsetzung Die Gonarthrose verursacht beträchtliche Morbidität und hohe Kosten für das Gesundheitssystem und die Gesellschaft. Die Eingriffsraten bei Knieendoprothesen variieren geografisch deutlich, mutmaßlich aufgrund fehlender standardisierter Indikationskriterien. Unser Ziel war die Festlegung expliziter Indikationskriterien für das deutsche Gesundheitssystem bez. Gelenkersatz bei Gonarthrose anhand eines evidenzgeleiteten, transparenten Konsensprojekts unter Einbeziehung der relevanten Interessengruppen.Methoden Der Konsensstudie lag ein Mixed-Methods-Ansatz zugrunde, der systematische Übersichtsarbeiten, Delphi-Konsentierungen und Konferenzen mit Interessensvertretern umfasste. Als Konsenspanel wurden Vertreter medizinischer Fachgesellschaften, der Kostenträger und von Patientenvereinigungen nominiert. Als Konsensuskriterium galt eine Zustimmung von mindestens 70% und Ablehnung von weniger als 20% des Entscheidungsgremiums. Konsentiert wurden (1) Hauptkriterien für die Indikationsstellung (zwingend notwendig), (2) Nebenkriterien für die Indikationsstellung (nicht zwingend notwendig), (3) absolute Kontraindikationskriterien sowie (4) Risikofaktoren, die mit einem schlechteren Outcome einhergehen.Ergebnisse Die folgenden 5 Hauptkriterien wurden konsentiert: 1. mehrfach wöchentlich intermittierend auftretende oder kontinuierliche Knieschmerzen über mindestens 3 – 6 Monate; 2. radiologischer Nachweis eines Strukturschadens (Arthrose, Osteonekrose); 3. Versagen konservativer medikamentöser und nicht medikamentöser Therapiemaßnahmen über mindestens 3 – 6 Monate; 4. eine auf die Kniegelenkerkrankung bezogene Einschränkung der Lebensqualität über mindestens 3 – 6 Monate; 5. auf die Kniegelenkerkrankung bezogener subjektiver Leidensdruck. Nebenkriterien für die Indikationsstellung, absolute Kontraindikationen und Risikofaktoren wurden ebenfalls mit hoher Übereinstimmung durch die Interessengruppen konsentiert.Schlussfolgerung Die definierten Indikationskriterien stellen eine Voraussetzung für den bedarfsgerechten Einsatz des endoprothetischen Gelenkersatzes bei Patienten mit Gonarthrose in Deutschland dar. Bei Patienten, welche die 5 Hauptkriterien erfüllen, sollte die tatsächliche Therapieentscheidung partizipativ durch Arzt und Patient erfolgen. Die konsentierten Indikationskriterien sollten nun im deutschen Gesundheitssystem implementiert werden. Weiterhin sollte eine prospektive Untersuchung von Prädiktoren für einen Therapieerfolg im Kontext der Routineversorgung erfolgen.
Keywords: knee osteoarthritis; total knee arthroplasty; indication; consensus; evidence